Reversible splenial lesion syndrome after blood transfusion presents callosal disconnection syndrome: A case report. Issue 24 (June 2018) - Ma, Xinxin; Su, Wen; Chen, Haibo
Abstract: Rationale: Reversible splenial lesion syndrome (RESLES) is a reversible condition with an excellent prognosis in most patients. The clinical features include altered states of consciousness, delirium, headache, and seizures, but no callosal disconnection syndromes have been described in RESLES. Patient concerns: We presented a 57-year-old patient with alien hand syndrome, autotopagnosia, gait disorders, and left ideomotor apraxia after blood transfusion. The brain magnetic resonance imaging (MRI) showed a few regions with high signal intensity in the genu, body, and splenium of the right corpus callosum on diffusion weighted images. Cerebrovascular examination was unremarkable. Diagnoses: He was diagnosed with RESLES and callosal disconnection syndrome. Interventions: The patient received symptomatic and supportive treatment in our hospital. Outcomes: He recovered to baseline on following up of 6 months and abnormalities on brain MRI completely disappeared. Lessons: Neurologists should be aware of the symptoms of callosal disconnection syndrome in RESLES. In addition, caution should be taken when transfusing blood products in patients with gastrointestinal bleeding.